At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Given Equation:
[tex]\[ \frac{x}{x-2} + \frac{x-1}{x+1} = -1 \][/tex]
Step 1: Combine the fractions on the left-hand side.
To combine the fractions, we need a common denominator, which is [tex]\((x-2)(x+1)\)[/tex].
[tex]\[ \frac{x(x+1) + (x-1)(x-2)}{(x-2)(x+1)} = \frac{x(x+1) + (x-1)(x-2)}{(x-2)(x+1)} \][/tex]
Step 2: Simplify the numerators.
Expand the numerators of both fractions:
[tex]\[ x(x+1) = x^2 + x \quad \text{and} \quad (x-1)(x-2) = x^2 - 3x + 2 \][/tex]
Now combine these:
[tex]\[ x^2 + x + x^2 - 3x + 2 = 2x^2 - 2x + 2 \][/tex]
So the fraction becomes:
[tex]\[ \frac{2x^2 - 2x + 2}{(x-2)(x+1)} = -1 \][/tex]
Step 3: Solve the equation by clearing the fraction.
Multiply both sides of the equation by [tex]\((x-2)(x+1)\)[/tex] to clear the denominator:
[tex]\[ 2x^2 - 2x + 2 = -1 \cdot (x-2)(x+1) \][/tex]
Simplify the right-hand side:
[tex]\[ -1 \cdot (x-2)(x+1) = -(x^2 - x - 2) \][/tex]
[tex]\[ -(x^2 - x - 2) = -x^2 + x + 2 \][/tex]
So now we have:
[tex]\[ 2x^2 - 2x + 2 = -x^2 + x + 2 \][/tex]
Step 4: Combine like terms to form a polynomial equation.
Move all terms to one side to set the equation to zero:
[tex]\[ 2x^2 - 2x + 2 + x^2 - x - 2 = 0 \][/tex]
Combine the like terms:
[tex]\[ 3x^2 - 3x = 0 \][/tex]
Step 5: Factor the resulting equation.
[tex]\[ 3x(x - 1) = 0 \][/tex]
The solutions to this equation are found by setting each factor to zero:
[tex]\[ 3x = 0 \quad \text{or} \quad x - 1 = 0 \][/tex]
Therefore,
[tex]\[ x = 0 \quad \text{or} \quad x = 1 \][/tex]
Thus, the solutions to the equation are:
[tex]\[ x = 0 \quad \text{or} \quad x = 1 \][/tex]
[tex]\[ \frac{x}{x-2} + \frac{x-1}{x+1} = -1 \][/tex]
Step 1: Combine the fractions on the left-hand side.
To combine the fractions, we need a common denominator, which is [tex]\((x-2)(x+1)\)[/tex].
[tex]\[ \frac{x(x+1) + (x-1)(x-2)}{(x-2)(x+1)} = \frac{x(x+1) + (x-1)(x-2)}{(x-2)(x+1)} \][/tex]
Step 2: Simplify the numerators.
Expand the numerators of both fractions:
[tex]\[ x(x+1) = x^2 + x \quad \text{and} \quad (x-1)(x-2) = x^2 - 3x + 2 \][/tex]
Now combine these:
[tex]\[ x^2 + x + x^2 - 3x + 2 = 2x^2 - 2x + 2 \][/tex]
So the fraction becomes:
[tex]\[ \frac{2x^2 - 2x + 2}{(x-2)(x+1)} = -1 \][/tex]
Step 3: Solve the equation by clearing the fraction.
Multiply both sides of the equation by [tex]\((x-2)(x+1)\)[/tex] to clear the denominator:
[tex]\[ 2x^2 - 2x + 2 = -1 \cdot (x-2)(x+1) \][/tex]
Simplify the right-hand side:
[tex]\[ -1 \cdot (x-2)(x+1) = -(x^2 - x - 2) \][/tex]
[tex]\[ -(x^2 - x - 2) = -x^2 + x + 2 \][/tex]
So now we have:
[tex]\[ 2x^2 - 2x + 2 = -x^2 + x + 2 \][/tex]
Step 4: Combine like terms to form a polynomial equation.
Move all terms to one side to set the equation to zero:
[tex]\[ 2x^2 - 2x + 2 + x^2 - x - 2 = 0 \][/tex]
Combine the like terms:
[tex]\[ 3x^2 - 3x = 0 \][/tex]
Step 5: Factor the resulting equation.
[tex]\[ 3x(x - 1) = 0 \][/tex]
The solutions to this equation are found by setting each factor to zero:
[tex]\[ 3x = 0 \quad \text{or} \quad x - 1 = 0 \][/tex]
Therefore,
[tex]\[ x = 0 \quad \text{or} \quad x = 1 \][/tex]
Thus, the solutions to the equation are:
[tex]\[ x = 0 \quad \text{or} \quad x = 1 \][/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.